Grapevine (Vitis vinifera L., cv. Pinotage) responses to water deficit modulated by rootstocks - Serra Stepke, Ignacio M. (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD(Agric))--Stellenbosch University, 2014.